Strategic human resource management - Mello, Jeffrey A. (Cencage Learning Asia Pte Ltd, 2019)
MindTap Management for Mello's Strategic Human Resource Management, 5th Edition is the digital learning solution that powers students from memorization to mastery. It gives you complete control of your course-to provide engaging content, to challenge every individual, and to build their confidence. Empower students to accelerate their progress with MindTap. MindTap: Powered by You. MindTap gives you complete ownership of your content and learning experience. Customize the interactive syllabi, emphasize the most important topics, and add your own material or notes in the eBook. Additional readings and associated questions, plus end-of-chapter quizzes will provide students with the opportunity to prove their decision-making and critical thinking skills. The outcome-driven application helps you challenge every student, build their confidence, and empower them to be unstoppable.